Zero-Effort Payments: Design, Deployment, and Lessons - Smowton, Christopher; Lorch, Jay; Molnar, David; Saroiu, Stefan; Wolman, Alec (Proceedings of the ACM International Joint Conference on Pervasive and Ubiquitous Computing (UbiComp), 2014)
This paper presents Zero-Effort Payments (ZEP), a seamless mobile computing system designed to accept payments with no effort on the customer’s part beyond a one-time opt-in. With ZEP, customers need not present cards nor operate smartphones to convey their identities. ZEP uses three complementary identification technologies: face recognition, proximate device detection, and human assistance. We demonstrate that the combination of these technologies enables ZEP to scale to the level needed by our deployments. We designed and built ZEP, and demonstrated its usefulness across two real-world deployments lasting five months of continuous deployment, and serving 274 customers. The different nature of our deployments stressed different aspects of our system. These challenges led to several system design changes to improve scalability and fault-tolerance.